PENGARUH ATMOSFER TOKO, PROMOSI DAN PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN DI INDOMARET TLOGOMAS - M. Amin Ilyas; Muhammad Hufron (UNIVERSITAS ISLAM MALANG, 2017)
ABSTRACTThe purpose of this study is to know and analyze the influence of StoreAtmosphere, Promotion and Service to Purchase Decision in Indomaret Tlogomas No19-20 Malang. Population in Research All consumers Indomaret Tlogomas No 19-20Malang. The sample used is consumer Indomaret Tlogomas No 19-20 Malang. Thesampling technique that is accidental sampling and samples in this study as much as 99respondents.Based on the results of this study it is known that the independent variablessimultaneously affect Significant to the dependent variable known value F arithmetic20.344 with the value of sig 0,000 <0.05 then H1 received, meaning the variableAtmospheric store, Promotion and Service simultaneously affect the Purchase Decision.And the variable Atmospheric store, known value t Count 4.050 with a value of 0.000sig, <0.05 means partial effect partially purchase decision. Promotional variable isknown value of t arithmetic 4,636 with value sig 0,000 <0,05 meaning promotionvariable partially influence to decision of purchase. Service Variables is known value oft arithmetic 5,776 with value of sig 0,000 <0,05 meaning service variable partiallyinfluence to purchasing decision.Keywords: Store Atmosphere, Promotion, Service and Purchase Decision.